EVALUASI KESESUAIAN LAHAN KELAPA SAWIT PADA LAHAN GAMBUT DI PESISIR SELATAN, SUMATERA BARAT - Arifin, Syamsul; Nugraha, Irfan Nur Priya; Al Jauhary, Muhammad Rifqi; Putra, Aditya Nugraha; Riza, Sativandi; Setiawan, Adi; Andhika, Yosi; Adril, Adril; Rayes, Mochtar Luthfi (Departemen Tanah, Fakultas Bio-industri Pertanian dan Kehutanan, Universitas Brawijaya, 2026)
Indonesia's current population growth rate has reached 1.13% per year, leading to increased demand for land and consequent land use conversion, including peatlands. The conversion of peatlands into oil palm plantations raises several negative issues, such as increased carbon emissions. Therefore, it is crucial to consider the characteristics of peatlands when determining their suitability for crop cultivation. This study aims to assess peat quality, nutrient retention, and soil classification in the research area and evaluate the suitability of peatlands for oil palm cultivation in Pancung Soal. The research was conducted in an oil palm plantation in Nagari Tluk Amplu Inderapura, West Sumatra, using a survey method and parameters such as peat depth, ash content, and pH. The boundaries of land suitability classes were determined based on oil palm production results. The findings indicate variations in peat quality, nutrient retention, and suitability for oil palm cultivation. The analysis initially reveals land suitability classes ranging from S3 to N. However, with modifications to certain parameters, the suitability classes can be improved to S2 and S3. These results approximate suitability based on actual field productivity. Boundary delineation for specific parameters is necessary to enhance land suitability for oil palm in the region.